Who's up to the challenge? 49

Calculus Level 5

0 1 x Li 2 ( x 2 1 ) d x \large \int _{ 0 }^{ 1 }{ x\text{Li}_2(x^2-1) \, dx }

If the integral above can be expressed as [ a b + π c d ] + ln f , -\left[ \dfrac { a }{ b } +\dfrac { { \pi }^{ c } }{ d } \right] +\ln { f },

where a , b , c , d a,b,c,d and f f are positive integers, with a , b a,b coprime, find a + b + c + d + f a+b+c+d+f .

Notation :
Li n ( a ) { \text{Li} }_{ n }(a) denotes the polylogarithm function, Li n ( a ) = k = 1 a k k n . { \text{Li} }_{ n }(a)=\displaystyle\sum _{ k=1 }^{ \infty }{ \frac { { a }^{ k } }{ { k }^{ n } } }.


The answer is 31.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

\begin{aligned} I & = \int_0^1 x\ce{Li}_2 (x^2-1) \, dx \\ & = \int_0^1 x \sum_{n=1}^\infty \frac{( \color{#3D99F6}{x^2-1})^n}{n^2} \, dx \quad \quad \small \color{#3D99F6}{\text{Let } u = x^2 - 1 \, \implies du = 2x dx} \\ & = \frac{1}{\color{#3D99F6}{2}} \int_\color{#3D99F6}{-1}^\color{#3D99F6}{0} \sum_{n=1}^\infty \frac{\color{#3D99F6}{u}^n}{n^2} \, d\color{#3D99F6}{u} \\ & = \frac{1}{2} \sum_{n=1}^\infty \frac{u^{n+1}}{n^2(n+1)} \bigg|_{-1}^0 \\ & = \frac{1}{2} \sum_{n=1}^\infty \frac{(-1)^n}{n^2(n+1)} \quad \quad \small \color{#3D99F6}{\text{By partial fractions}} \\ & = \frac{1}{2} \sum_{n=1}^\infty \left(\frac{(-1)^n}{n^2} - \frac{(-1)^n}{n} + \frac{(-1)^n}{n+1} \right) \\ & = \frac{1}{2} \left(\sum_{n=1}^\infty \frac{(-1)^n}{n^2} - \sum_{n=1}^\infty \frac{(-1)^n}{n} - \sum_{n=2}^\infty \frac{(-1)^n}{n} \right) \\ & = \frac{1}{2} \left(\sum_{n=1}^\infty \frac{(-1)^n}{n^2} - 2 \sum_{n=1}^\infty \frac{(-1)^n}{n} - 1 \right) \\ & = \frac{1}{2} \sum_{n=1}^\infty \frac{(-1)^n}{n^2} - \sum_{n=1}^\infty \frac{(-1)^n}{n} - \frac{1}{2} \\ & = -\frac{1}{2} \left( \sum_{n=1}^\infty \frac{1}{n^2} - \frac{2}{4} \sum_{n=1}^\infty \frac{1}{n^2} \right) + \ln 2 - \frac{1}{2} \\ & = -\frac{1}{4} \zeta(2) + \ln 2 - \frac{1}{2} \\ & = - \left[\frac{1}{2} + \frac{\pi^2}{24}\right] + \ln 2 \end{aligned}

a + b + c + d + f = 1 + 2 + 2 + 24 + 2 = 31 \implies a + b + c + d + f = 1 + 2 + 2 + 24 + 2 = \boxed{31}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...